Oral corticosteroid-sparing effects of mepolizumab in severe eosinophilic asthma: evidence from randomized controlled trials and real-world studies. (August 2022) - Casale, Thomas B.; Burnette, Autumn; Bourdin, Arnaud; Howarth, Peter; Hahn, Beth; Stach-Klysh, Alexandra; Khurana, Sandhya
Oral corticosteroids (OCS) have long been a mainstay of treatment for asthma exacerbations and chronic severe asthma. However, it is increasingly recognized that both long-term and short-term OCS use are directly associated with a wide range of serious adverse effects, and as such OCS-sparing treatment alternatives are now widely recommended for patients with severe asthma. While several international guidelines recommend these treatments, guidance on OCS tapering, and which patients are most likely to tolerate OCS reduction and/or discontinuation, is still lacking. Several biologics have demonstrated efficacy in patients with OCS-dependent asthma. One OCS-sparing treatment is the anti-interleukin-5 monoclonal antibody mepolizumab, which is approved for the treatment of severe eosinophilic asthma. In addition to improved exacerbation rates, asthma control, quality of life, and lung function among patients with severe eosinophilic asthma, mepolizumab also has an OCS-sparing effect, which has been demonstrated in randomized controlled trials and real-world studies. Both physicians and patients express concerns about the adverse effects of OCS, and additional data from the randomized, controlled SIRIUS trial (NCT01691508) highlight the high level of concern among patients regarding OCS-related burden. In this article, we discuss current guidance on OCS-sparing strategies for patients with severe asthma, provide a summary of the available evidence of the OCS-sparing effect of mepolizumab, and highlight patient and physician perspectives on the use of OCS and OCS-sparing treatments in severe asthma.